Preventing Money Laundering Through The Know Your Customer Principle by Indonesian Notary in Foundation Establishment - Irawan, Randyarsa Nurindra (Fakultas Hukum Universitas Airlangga, 2025)
According to Indonesian law, foundation is a legal entity consisting of segregated assets intended to achieve certain social, religious, and humanitarian goals, which has no members. The establishment of a foundation in Indonesia has three important stages, namely establishment, ratification, and announcement. The first stage, the establishment of the foundation must be based on the deed of establishment made by an Indonesian Notary. The second stage, the ratification of the foundation, is authorized by the Minister of Law and Human Rights of Indonesia. The third stage, namely the foundation, must be immediately announced in the Supplement to the State Gazette of the Republic of Indonesia. The main regulation relating to foundations in Indonesia is Law Number 28 of 2004 concerning Amendments to Law Number 16 of 2001 concerning Foundations. In order to prevent money laundering, preventive measures such as Know Your Customer Principle must be taken in the process of establishing a foundation. Know Your Customer Principle supports the principle of accountability of a foundation in knowing the source of funds used in the foundation. The purpose of this study is to analyze the application of Know Your Customer Principle in the foundation establishment stage in Indonesia and the challenges of Know Your Customer Principle application in the foundation establishment stage in Indonesia. This type of research is normative legal research with a statutory research approach, conceptual approach, and comparative approach that compares foundation establishments in Indonesia and Malaysia. The implication of this problem is that in the foundation establishment stage, if the application of Know Your Customer Principle is not carried out firmly, considering the large number of foundations that are established, it can cause the potential for a foundation not to be optimally supervised such as sources of funds derived from money laundering crimes. There needs to be a superior institution that supervises foundations facilitated by the State, so that foundations in the future can be controlled and do not commit fraudulent acts. Indonesian notary are one of the parties that have an important role in carrying out Know Your Customer Principles, so that the accountability of a Notary in Indonesia will also be involved in the context of establishing a foundation.